Photocurrent in Bi2Se3 films electrodeposited with predominance of the orthorhombic phase - Franca, José Romão; Souza, Paloma Boeck; Dias, Juliana Gonçalves; Perdomo, Andrés David Pardo; Linhares, Alexandro Amorim; Bassoli, William Renan Basso; Schafer, Deise; Pasa, André Avelino; Cid, Cristiani Campos Plá (Electrochimica acta, 2023)
Binary compound bismuth selenide (Bi2Se3) in the orthorhombic phase is an n-type semiconductor with optoelectronic properties desirable for applications in photosensitive devices. Obtaining this phase at room temperature is challenging, resulting in limited literature on the subject, thereby restricting the available information about this phase. In this study, we present our findings on the aqueous medium synthesis and stability of nanocrystalline Bi2Se3 thin films over a Si substrate, predominantly exhibiting an orthorhombic phase (>92%), utilizing the electrodeposition technique. By changing the concentration of the electrolyte and deposition potential, it was possible to modify the morphology, absorbance, optical gap, and the magnitude of photocurrent signal in the photoelectrochemical cell (PEC), with no dramatical change in the chemical composition and crystalline phase of the films. The samples presented an inverse correlation between crystallite size and band gap, associated with the deposition conditions. Stability in the transient photocurrent signal with amplitudes around 9 µA/cm2 at 0.30 VSCE was observed for the sample growth at more negative potential.